Bacterial contamination of the hands of food handlers as indicator of hand washing efficacy in some convenient food industries - Lambrechts, A.A.; Human, I.S.; Doughari, J.H.; Lues, JFR (Pakistan Journal of Medical Sciences, 2014)
Hands of ready-to-eat food service employees have been shown to be vectors in the spread of foodborne disease, mainly because of poor personal hygiene and accounting for approximately 97% of food borne illnesses in food service establishments and homes. Our objective was to evaluate the efficacy of hand washing practices and sanitation before commencing work among food handlers in the convenient food industry in Gauteng, South Africa. Methods: A total of 230 samples were collected, involving 100% of the food handlers, in 8 selected convenient food outlets with their main focus on preparing ready-to-eat foods. The workers’ cleaned and disinfected dominant hands were sampled for Total Plate Count (TPC), Staphylococcus aureus and Escherichia coli. Bacteria were isolated and counted using standard methods. Results: The highest bacterial count from the hand samples was 7.4 x 103 cfu.cm-2 and the lowest showed no detectable growth. Although hands with a count of 0 cfu.cm-2 were found in all of the plants, the results indicated that all the plants exceeded the legal limit for food surfaces or hands of < 100 cfu.cm-2 when the average bacterial counts on hands were compared. Sixty percent of the TPC analysed exceeded the legal limit and only 18% of the food handlers had no bacteria detectable on their hands. One sample tested positive for E. coli and S. aureus could not be detected on the hands of any of the food handlers. Conclusion: The study revealed that hand hygiene is unsatisfactory and may have serious implications for public health due to contamination of food from food handlers’ hands. This therefore underlined the importance of further training to improve food handlers’ knowledge of good hand washing practices.
Published Article
Keywords: Hand washing; Hygiene; Food handlers; Contamination; S. aureus; E. coli